Hexagon Model: Financial Statement Fraud (Evidence Indonesian Health Company) - Satria, Hendy; Chartady, Rachmad; Nurililah, Zulfadhia (Jurnal Ilmiah Akuntansi Universitas Pamulang, 2024)
This research aims to determine the effect of the fraud hexagon model on financial statement fraud in healthcare companies listed on the Indonesia Stock Exchange for the 2019-2022 period. This research used a sample of 16 companies using a sampling technique, namely purposive sampling. The method used in this research is a quantitative descriptive method. The object of this research is a healthcare company listed on the Indonesian Stock Exchange. Data collection techniques were carried out using documentation and literature study methods. The results of this research are based on the results of the t-test or partial test which shows that pressure, capability, and rationalization affects fraudulent financial statements. Opportunity, arrogance, and collusion do not affect financial statement fraud. The results of the f test or simultaneous test show that pressure, capability, opportunity, rationalization, arrogance, and collusion together simultaneously influence financial statement fraud. It can be concluded that the results of the coefficient of determination test with a McFadden R-squared value of 0.2313, which means that the variables pressure, capability, opportunity, rationalization, arrogance, and collusion influence financial statement fraud by 23.13% while the remaining 76.87% is influenced by other external variables from the research studied.